PENGARUH KOMPETENSI MANAJERIAL DAN SUPERVISI KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU - Lelah; Djam’an Satori; Kania Agustina (DIALOGIKA, 2020)
The purpose of this study was to analyze the effect of managerial competence and supervision on teacher performance. In this study, the research method used by the author in this study is an empirical study method, namely research on empirical facts obtained based on observation and experience. The sample in this study were all teachers at three SMPN Banjaran with the technique of taking it by census, that is, the entire population was used as the research sample. The analysis technique used in this research is correlational. Managerial competence based on the results of hypothesis testing statistically shows a positive and significant effect on teacher performance. Principal supervision activities based on the results of statistical hypothesis testing showed a positive and significant effect on teacher performance. Managerial competence and supervision of principals based on the results of statistical hypothesis testing simultaneously show a positive and significant effect on teacher performance